2014
DOI: 10.1074/jbc.m114.576843
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evolution of the Tissue-nonspecific Alkaline Phosphatase Allows Prediction and Validation of Missense Mutations Responsible for Hypophosphatasia

Abstract: Background:We used evolutionary analysis of alkaline phosphatase (tissue nonspecific alkaline phosphatase, TNSALP) to predict missense mutations leading to hypophosphatasia. Results: We found 469 sensitive positions and validated 99% of the 204 known mutations. Conclusion: It is a more powerful method than in silico models to validate missense mutations in TNSALP. Significance: Such an approach should be widely used to support genetic diagnostics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 46 publications
5
60
0
Order By: Relevance
“…The inheritance mechanism can be autosomal recessive or dominant. About 80 % of the known mutations are missense point mutations, 10 % are small deletions, 4 % splicing mutations, 3 % nonsense mutations, 2 % small insertions, and ≤1 % complex insertion/deletions, large deletions, or mutations in the regulatory sequence [21,23,24].…”
Section: Geneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inheritance mechanism can be autosomal recessive or dominant. About 80 % of the known mutations are missense point mutations, 10 % are small deletions, 4 % splicing mutations, 3 % nonsense mutations, 2 % small insertions, and ≤1 % complex insertion/deletions, large deletions, or mutations in the regulatory sequence [21,23,24].…”
Section: Geneticsmentioning
confidence: 99%
“…The ALPL gene consists of 12 exons distributed over 50 kilobases [19,20]. Human TNSALP is a chain of 524 amino acid residues [21]. The genes of the other, tissue-specific, ALP isoenzymes are located on the long arm of chromosome 2 (2q34-37) [22].…”
Section: Geneticsmentioning
confidence: 99%
“…However, early lethality of these mice limits analyses to developmental stages, precluding longer-term studies on tooth function, dentoalveolar remodeling, repair, and regeneration. One approach to resolve this limitation was creation of a knock-in mouse harboring a dominant-negative human ALPL mutation associated with odontohypophosphatasia (Hu et al 2000;Silvent et al 2014). Alpl +/A116T mice featured 50% reduced plasma ALP and no apparent skeletal defects, and they lived to be >1 y old .…”
Section: Dental Defects In Mouse Models Of Late-onset Hppmentioning
confidence: 99%
“…Genotype-phenotype correlation studies have demonstrated that loss-of-function variants typically cause severe forms, while missense changes often result in milder forms. The protein product of ALPL is tissue nonspecific (liver/bone/ kidney) alkaline phosphatase, an enzyme that is essential for calcium and phosphorus mineralization in developing bones and teeth [Silvent et al, 2014].…”
Section: Molecular Findingsmentioning
confidence: 99%